Natyamandapa: A Real or a Fictional Performing Space of the Classical Indian Theatre - Gönc Moačanin, Klara (Array, 2003)
The question whether theatre buildings ever existed in ancient India or their description in the Natyasastra is a fictive description of an ideal space, has not found a satisfactory answer until now. After discussing several terms referring to the theatre (and explaining e.g. the mattavarani as a fence separating the sacred space of the stage from the profane public), the author says: "There is only an ideal model from Natyasastra which, in my opinion, represents sacred space which conforms to the rules for building a temple as found in silpasastras." Therefore she is preliminarily inclined to subscribe to Levi's view that theatre in India always remained "un plaisir de circonstance" and never had a specialized building. However, she supposes that a mulitidisciplinary research of this question could yield more trustworthy results than those that have been achived so far.